Ventricular septal rupture: successful delayed repair. Issue 6 (1st November 2016) - Claus, Isabelle; Cathenis, Koen; Goossens, Dominique; Ballaux, Philippe
Abstract: Ventricular septal rupture (VSR) occurs in approximately 1% of the patients who experience an acute myocardial infarction. The operative mortality of VSR repair decreases if surgery can be delayed until the infarct has healed and tissue strength improved. Because of heart failure or impending cardiogenic shock, surgical treatment can often not be delayed. We present a case in which a delayed repair of a VSR was possible. The patient was initially stabilized with an intra-aortic balloon pump. She was discharged and readmitted 5 weeks later for definitive repair. Repair was performed, according to the Daggett technique, using a bovine pericardial patch and a mitral annuloplasty was carried out to correct for the regurgitation. Recovery was uneventful. Cardiac ultrasound examination at discharge showed no residual defect.